2014
DOI: 10.1002/gepi.21831
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Analysis Approaches for Rare and Common Variants: Insights From Genetic Analysis Workshop 18

Abstract: Pathway analysis, broadly defined as a group of methods incorporating a priori biological information from public databases, has emerged as a promising approach for analyzing high-dimensional genomic data. As part of Genetic Analysis Workshop 18 (GAW18), seven research groups applied pathway analysis techniques to whole genome sequence data from the San Antonio Family Study. Overall, the groups found that the potential of pathway analysis to improve detection of causal variants by lowering the multiple testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Using the observed cell proportions remains the best way to remove this effect as much as possible [ 17 ]. Moreover, certain methodological considerations in pathway analysis including the fact that annotation of genetic variants is inconsistent across databases, incomplete and biased toward known genes must be noted [ 29 ]. The gold standard to establish validity of findings from pathway analysis remains the replication of results in independent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using the observed cell proportions remains the best way to remove this effect as much as possible [ 17 ]. Moreover, certain methodological considerations in pathway analysis including the fact that annotation of genetic variants is inconsistent across databases, incomplete and biased toward known genes must be noted [ 29 ]. The gold standard to establish validity of findings from pathway analysis remains the replication of results in independent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis can be described as “a group of statistical methods that exploit a priori knowledge of pathways” [ 94 ]. It forms the link between ‘omics’ results and the phenotype/disease under study and provides a biological meaning to the genes and variants detected (interpretation of results).…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, it reduces the multiple-testing burden and, thus, offers a huge analysis potential. Aslibekyan et al [ 94 ] showed that in spite of the great potential of pathway analysis, there are still many obstacles to overcome (for example, due to the lack of a golden analysis standard).…”
Section: Reviewmentioning
confidence: 99%
“…For almost two decades, the class of pathway analysis methods [e.g., GSEA; ( Subramanian et al, 2005 )] have been proposed as methods for aggregating gene-based summary statistics across multiple genes within a biologically defined set (e.g., a pathway). Although many of the original pathway analysis methods were developed for use on gene-expression data, the application of these methods to sequencing data has been proposed ( Wu et al, 2010 ; Wu and Zhi, 2013 ) and applied specifically to analyze rare variants ( Aslibekyan et al, 2014 ; Moore et al, 2016 ; Richardson et al, 2016 ; Larson et al, 2017 ). These approaches first conduct gene-based tests of association and then use methods to aggregate the gene-level test statistics ( Petersen et al, 2011 ; Aslibekyan et al, 2014 ; Valcarcel et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%